Professional presentations : a video-based course : teacher's guide - Goodale, Malcolm (Cambridge : Cambridge University Press, 1998)
This book contains comprehensive teaching notes, and photocopiable tasks and videoscripts to give to learners for the four parts of the Video.
Keywords: Business; Business presentations; Public speaking; Oral communication